Attendance at the 6th Annual Library Leadership Institute, 18-22 April 2008, at Shantou - Suja', Balqis (Persatuan Pustakawan Malaysia, 2008)
This a report of an institute on library leadership (based at the Hong Kong University) with a format of eight lectures, each followed by 20 to 30-minute break-out sessions, and a case study that formed a crucial part of the program; each team was assigned a case study topic. Within the presentations, topics and themes covered include: Strategic planning, effective leadership, organizational change, learning commons concept, promoting and supporting Web 2.0 services on campus, new generation users, Library 2.0 phenomenon, social software and networking, scholarly communications, transformative technologies and a discovery culture, and state-of-the art of libraries international trends.